Building A Training Programme On The Dimensions Of Accountants' Professional Motivation And Its Impact On The Development Of Technical Literacy - Mohammed Kadhim Al-Abboodi; Mondher Fakhfakh (Harmoni Economics: International Journal of Economics and Accounting, 2024)
The research aims to build a training programme according to the dimensions of the professional motivation of accountants and its impact on the development of technical Literacy by verifying the validity of the following null hypothesis: "There is no statistically significant difference at the level of significance (0.05) between the average scores of accountants of the experimental group and those who will subject accountants to the training programme based on the dimensions of professional motivation and the average scores of accountants for the control group who will not subject accountants to training in the training programme in technical Literacy.To achieve the objectives of the research, the researchers used the experimental design with two equivalent groups (experimental and control), as 42 accountants were randomly selected (by lot) as a sample for research from the accountants of the General Directorate of Education of Qadisiyah for the academic year 2024-2025, by 21 accountants for the experimental group and 21 accountants for the control group.The training programme was built according to three stages (planning, design, evaluation), and then trained accountants of the experimental group for a period of (11) days by two sessions per day using the training programme according to the dimensions of professional motivation, and the researcher prepared a scale for technical Literacy of the type of multiple choice (40 items), and their sincerity and stability were verified, as the stability coefficient for testing the scale reached (90, 0) and the stability coefficient of the observation card was (0.86), for the scale test (0.89) and they were applied after the end of the experiment. And the researcher used the statistical programme SPSS.The accountants of the experimental group outperformed the accountants of the control group in the scale test, and in light of the results of the research, the researcher recommended the possibility of adopting the training programme prepared according to the dimensions of professional motivation.